Economic Value of Fruit Trees as Shading Trees and CO2 Sequestration. Issue 1 (May 2020) - Ali, S; Gunawan, T; Maryono, A; Hindrayani, A
Abstract: As function as shading trees and CO2 sequestration, fruit trees as agricultural commodities were grown in residential. This study aims to identify the fruit species that has the function of CO2 sequestration in minimizing the effects of air pollution caused by domestic pollutants in the housing and also has high economic value. This research used survey method to test model CO2 calculation mathematically with Takaoki Method and convert the production of CO2 by the house. Samples were fruit trees planted in residential area in Yogyakarta. The results showed that there were several types of fruit trees that have high CO2 sequestration namely Pometia pinnata, Artocarpus integra and Eugenia aquea, which was recommended to be planted in order to reduce pollutants in the domestic housing and has high economic value.